Optimization of Trigona Honey and Coating Material Formulations for Antioxidants and Physical Properties of Microencapsulation of Coriander Seed Extract Using the D-Optimal Mixture Method - Muttaqin, Irfan; Taufik, Yusman; Ikrawani, Yusep (Publisher Cv. Inara, 2023)
The purpose of this study was to produce an optimal formulation of coriander seed extract microencapsulation products using the Mixture D-Optimal Design Expert program.The study consists of two stages. The first stage was the analysis of the coriander seed extract powder using the spray drying method without the use of coating materials and honey. The second stage was to determine the optimal formula using the D-Optimal Mixture method of Design Expert program through measurement of chemical responses (antioxidant activity, and water content), physical response. (particle size). The optimum formula obtained based on the Design Expert program with the D-Optimal Mixture method has a desirability value of 1 with the prediction value of each response being 395.124 ppm antioxidant activity, 2.329 % water content, and 2.967 µm particle size.